How Open Source Is Changing the Software Developer's Career. - Riehle, Dirk (Computer (00189162), 2015)
Software developers with open source project experience acquire verifiable technical expertise, peer-certified competencies, and positional power--advantages that align with companies' need to obtain a competitive advantage.